2008
DOI: 10.1016/j.hrthm.2008.09.015
|View full text |Cite
|
Sign up to set email alerts
|

Atrial-selective effects of chronic amiodarone in the management of atrial fibrillation

Abstract: Background Although amiodarone is one of the most effective pharmacologic agents used in clinical management of atrial fibrillation (AF), little is know about its differential effects in atrial and ventricular myocardium. Objectives To compare the electrophysiological effects of chronic amiodarone in atria and ventricles. Methods We compared the electrophysiological characteristics of coronary-perfused atrial and ventricular wedge preparations isolated from untreated and chronic amiodarone-treated dogs (Am… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
101
2

Year Published

2009
2009
2020
2020

Publication Types

Select...
6
2
1

Relationship

2
7

Authors

Journals

citations
Cited by 64 publications
(110 citation statements)
references
References 30 publications
7
101
2
Order By: Relevance
“…Chronic administration of amiodarone depresses sodium channel-mediated parameters and prolongs action potential duration predominantly in the atria and thus contributes to suppression of AF. 29) However, the present study showed that intravenous administration of amiodarone had no effect on atrial MAPD and ERP but increased IACT in a rate-dependent manner. Therefore, intravenous administration of amiodarone may be of limited value for termination of AF in patients with electrically and structurally remodeled atria.…”
Section: Effects Of Class III Antiarrhythmic Drugs In the Remodeled Hcontrasting
confidence: 75%
“…Chronic administration of amiodarone depresses sodium channel-mediated parameters and prolongs action potential duration predominantly in the atria and thus contributes to suppression of AF. 29) However, the present study showed that intravenous administration of amiodarone had no effect on atrial MAPD and ERP but increased IACT in a rate-dependent manner. Therefore, intravenous administration of amiodarone may be of limited value for termination of AF in patients with electrically and structurally remodeled atria.…”
Section: Effects Of Class III Antiarrhythmic Drugs In the Remodeled Hcontrasting
confidence: 75%
“…Both ranolazine and amiodarone were shown to "take advantage" of these distinctions, producing significant depression of sodium channel-dependent parameters in canine atrial, but not in ventricular, preparations, thus leading to effective suppression of AF at concentrations causing minimal to no effect on ventricular electrophysiology (Burash- Sicouri et al, 2009;. The atrial selectivity of ranolazine as well as its anti-AF efficacy have been demonstrated in both in vitro and in vivo animal studies (Burashnikov et al, 2007;Kumar et al, 2009;Carvas et al, 2010;Szél et al, 2011) Atrial-selective depression of sodium channel-mediated parameters in the canine heart has also been reported with exposure to chronic amiodarone and acute tert-butyl (2-{7-[2-(4-cyano-2-fluorophenoxy)ethyl]-9-oxa-3,7-diazabicyclo[3.3.1]non3-yl} ethyl)carbamate (AZD1305) (Burashnikov et al, 2008. In a large clinical study in patients with non-ST segment elevation acute coronary syndrome (Scirica et al, 2007) treatment with ranolazine was associated with the reduced incidence of supraventricular arrhythmias and a 30% reduction in new onset AF.…”
Section: Discussionmentioning
confidence: 99%
“…Atrial-selective prolongation of APD 90 by ranolazine and propafenone is likely caused by their effect to block I Kr (Grant, 1996;Antzelevitch et al, 2004). Indeed, specific I Kr block with N- [4-[1-[2-(6-methylpyridin-2-yl) ethyl]piperidine-4-carbonyl]phenyl] (E-4031) produces atrialpredominant prolongation of APD 90 and ERP in canine preparations at a CL of 500 ms (Burashnikov et al, 2008). A similar atrial-predominant effect of I Kr blockers to prolong ERP has been demonstrated in vivo in both canine and porcine hearts (Spinelli et al, 1992;Wiesfeld et al, 1996).…”
Section: -Benzofuryl]-2-(propylamino)-ethanol Hydrochloride (Gementioning
confidence: 99%
“…antiarrhythmic drugs; sodium channel; blockade; mathematical models RANOLAZINE, an antianginal drug with antiarrhythmic properties, has been shown to effectively suppress atrial fibrillation (1)(2)(3)(4)(5) by producing potent atrial-selective use-dependent inhibition of Na ϩ current (I Na )-dependent parameters. The results of our experimental study presented in the accompanying paper (19) revealed that ranolazine is an open state blocker that displays almost no interaction with the inactivated state of the channel.…”
mentioning
confidence: 99%